2023
DOI: 10.3389/fmolb.2023.1223411
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and biochemical investigations of the anti-fatigue effects of tea polyphenols and fruit extracts of Lycium ruthenicum Murr. on mice with exercise-induced fatigue

Abstract: Background: The molecular mechanisms regulating the therapeutic effects of plant-based ingredients on the exercise-induced fatigue (EIF) remain unclear. The therapeutic effects of both tea polyphenols (TP) and fruit extracts of Lycium ruthenicum (LR) on mouse model of EIF were investigated.Methods: The variations in the fatigue-related biochemical factors, i.e., lactate dehydrogenase (LDH), superoxide dismutase (SOD), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-2 (IL-2), and interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 130 publications
0
5
0
Order By: Relevance
“…For instance, wolfberry flavonoid extract demonstrated antioxidant effects comparable to vitamin C and exhibited anti-inflammatory activity by curbing the production of nitric oxide and pro-inflammatory factors ( Yang et al, 2022 ). Additionally, L. ruthenicum extracts exhibited anti-inflammatory effects akin to those of tea polyphenols and reduced oxidative stress ( Bi et al, 2023 ). A positive correlation has also been established between phenolic content and the antioxidant capacities as measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azinobis- (3-ethylbenzthiazoline-6- sulphonate) (ABTS), and Ferric ion reducing antioxidant power (FRAP) assays ( Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, wolfberry flavonoid extract demonstrated antioxidant effects comparable to vitamin C and exhibited anti-inflammatory activity by curbing the production of nitric oxide and pro-inflammatory factors ( Yang et al, 2022 ). Additionally, L. ruthenicum extracts exhibited anti-inflammatory effects akin to those of tea polyphenols and reduced oxidative stress ( Bi et al, 2023 ). A positive correlation has also been established between phenolic content and the antioxidant capacities as measured by 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2′-Azinobis- (3-ethylbenzthiazoline-6- sulphonate) (ABTS), and Ferric ion reducing antioxidant power (FRAP) assays ( Jiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…LRM polysaccharides and tea polyphenols (TPs) exhibit anti-fatigue effects by reducing oxidative stress and inflammation [42,43]. Changes in fatigue-related biochemical factors lactic acid dehydrogenase (LDH), superoxide dismutase (SOD), tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), interleukin-2 (IL-2), and interleukin-6 (IL-6) were measured in motor fatigue (EIF) mouse models treated with TPs and LRPs.…”
Section: Anti-fatigue Propertiesmentioning
confidence: 99%
“…Inflammation is a marker of numerous diseases and is associated with infection and the immune system, accompanied by the production of inflammatory mediators, the proinflammatory cytokines such as tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, and IL-6 [35]. Anti-inflammatory effects have been reported for LRM [13][14][15]. Lu et al [16] evaluated the regulation of the expression of inflammation-related genes in response to LRM fruit extract treatment.…”
Section: Anti-inflammatory Effectsmentioning
confidence: 99%
“…Anti-Fatigue Activity Control of fatigue is crucial because such control can prevent the development of many serious health problems; indeed, fatigue is regarded as an intermediate condition between health and sickness [54]. Bi et al [15] reported that LRM fruit water extract has anti-fatigue activity. A total of 80 Kunming mice (sex ratio 1:1) were orally administered with distilled water (control group) or LRM fruit extract (0.05, 0.1, 0.2, or 0.5 mg/g water extract) once a day for 28 days.…”
Section: Immunomodulatory Effectsmentioning
confidence: 99%
See 1 more Smart Citation